OPTIMIZING LOCAL POTENTIAL THROUGH CO-PRODUCTION: A CASE STUDY OF PUTIKSARI INNOVATION IN MALANG, INDONESIA - Elis Mardianti; Muhammad Dzulfikar Al Ghofiqi; Bintoro Wardiyanto (Universitas Negeri Yogyakarta, 2025)
PUTIKSARI is one such community-based collaborative innovation in Indonesia. In recent years it has attracted national attention through several awards and its adoption as a replication model in other regions. This study examines how the programme is implemented by looking specifically at how local government actors understand and carry out co-production within the initiative. Using a qualitative interpretive approach, data were collected through semi-structured interviews with five officials from the subdistrict and village levels, supported by a review of relevant documents. The findings show that PUTIKSARI has gradually shifted the role of citizens from passive recipients of services to active contributors involved in planning, developing, and evaluating thematic village activities. The government notes several positive outcomes from this process, including stronger social legitimacy and better use of local village potential. However, implementation is not without challenges, particularly regarding the uneven participation of community groups and the limited involvement of private actors in programme support and evaluation. Based on these findings, the study suggests that local governments need to strengthen facilitation strategies to build community capacity and ensure broader and more consistent participation.